Kepemimpinan Inovatif dan Reformasi dalam Meningkatkan Sistem Informasi Manajemen (Cashless) di SMP Tahfidh Al Hidayah Kauman Kabupaten Tulungagung - Prastiwi, Meilinda Ade; Aziz, Abd.; Efendi, Nur (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research aims to explore the implementation of a cashless payment system (Cashless Management Information System) at SMP Tahfidh Al Hidayah, which was introduced in the 2024/2025 school year to improve the efficiency, security, and transparency of financial management. The focus of this research is the leadership of innovation and reform in improving the Management Information System. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis and the implementation of the research from August 23-October 13, 2024. The results showed that Innovation and Reform Leadership in Management Information System at SMP Tahfidh Al Hidayah Kauman Tulungagung Regency successfully integrated the Cashless SIM system as part of the long-term vision of a more modern school. The school environment supported by the cashless system includes several aspects of digital payment facilities, integrated management systems and accessibility of financial information. The findings from this study also provide practical recommendations for similar schools to improve the quality of education through innovative and reformist leadership strategies that focus on the implementation of cashless systems and are oriented towards operational efficiency.